Determinação de benzeno, tolueno, etilbenzeno e xilenos em gasolina comercializada nos postos do estado do Piauí - Silva, Flamys Lena do N. (2009)
Automotive gasoline consists of a complex mixture of flammable and volatile hydrocarbons derived from crude oil with carbon numbers within the range of 4-12 and boiling points range of 30-225 ºC. Its composition varies with the kind of crude oil and the type of refinery process that they undergone. Aromatics hydrocarbons, in particular benzene, toluene, ethylbenzene and isomeric xylenes (BTEX) are the toxic group constituents presents. GC-FID was employed to quantify these hydrocarbons in 50 commercial gasoline samples from Piauí state. Statistical analysis techniques, such as PCA and HCA were used to analyze the data. Moreover, several validation parameters were evaluated.